2020
DOI: 10.1177/0956462419890496
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of co-infections with other sexually transmitted infections in patients newly diagnosed with anogenital warts in Guangzhou, China

Abstract: Prevalence of co-infecting sexually transmitted infections (STIs) among patients newly diagnosed with anogenital warts is under-reported. Our objective is to determine the prevalence of six common STIs, Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG), genital herpes (herpes simplex virus type 2 [HSV-2]), HIV, and syphilis for patients visiting a sexual health clinic in Guangzhou, China. Demographics, sexual health, and medical histories were collected at patient intake. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…1 Previous studies showed that the majority of patients with AGWs who applied to the dermatology outpatient clinic are male patients (ranged 58.5%-88.8%). [6][7][8][9][10][11][12] In our study, the number of male patients (70.7%) was higher than female patients, consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…1 Previous studies showed that the majority of patients with AGWs who applied to the dermatology outpatient clinic are male patients (ranged 58.5%-88.8%). [6][7][8][9][10][11][12] In our study, the number of male patients (70.7%) was higher than female patients, consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Bacterial coinfections impact significantly on the process of pathogenesis and appearance of clinical manifestations [22,23]. It is also indicative that coinfections may be present in asymptomatic patients [24]. Compared to infections, coinfections change the process of inflammation in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Polymicrobial cervicitis, though rarely documented on cytology, is common among immunocompromised women, especially those who are HIV‐positive. HIV‐positive patients are at an increased risk of acquiring various sexually transmitted diseases, including bacterial vaginosis, trichomoniasis, candidiasis, chlamydial infection, herpes simplex virus type 2 (HSV‐2) infection and HPV infection 1,2 …”
Section: Discussionmentioning
confidence: 99%